A Molecular Approach to Immunoscintigraphy: A Study of the T-Antigen Conformation on the Surface of Tumors - Noujaim, A.; Selvaraj, S.; Suresh, M. R.; McLean, G.; Willans, D.; Turner, C.; Haines, D. M.; Longenecker, M. (Nuklearmedizin - NuclearMedicine, 1987)
The role of glycoconjugates in tumor cell differentiation has been well documented. We have examined the expression of the two anomers of the Thomsen-Friedenreich antigen on the surface of human, canine and murine tumor cell membranes both in vitro and in vivo. This has been accomplished through the synthesis of the disaccharide terminal residues in both a and ß configuration. Both entities were used to generate murine monoclonal antibodies which recognized the carbohydrate determinants. The determination of fine specificities of these antibodies was effected by means of cellular uptake, immunohistopathology and immunoscintigraphy. Examination of pathological specimens of human and canine tumor tissue indicated that the expressed antigen was in the β configuration. More than 89% of all human carcinomas tested expressed the antigen in the above anomeric form. The combination of synthetic antigens and monoclonal antibodies raised specifically against them provide us with invaluable tools for the study of tumor marker expression in humans and their respective animal tumor models.Die Rolle von Glykokonjugaten bei der Tumorzelldifferenzierung ist gut dokumentiert. Wir haben die Expression der zwei Anomere des Thomsen- Friedenreich-Antigens an der Oberfläche von Tumorzellmembranen des Menschen, Kaninchens, der Ratte und Maus sowohl in vitro als auch in vivo untersucht. Dies wurde durch die Synthese der Disaccharid-Endgruppen sowohl in Alphawie in Betakonfiguration bewerkstelligt. Beide Gruppen wurden dazu benutzt, um monoklonale Antikörper der Maus zu erzeugen, welche die Karbohydrat-Determinanten erkannten. Die Bestimmung von fünf Spezifitäten dieser Antikörper wurde anhand der zellulären Aufnahme, Immunhistopathologie und Immunszintigraphie vorgenommen. Die Untersuchung pathologischer Proben von Tumorgewebe des Menschen und Kaninchens zeigte, daß das exprimierte Antigen in der Betakonfiguration war. Mehr als 89% aller getesteten menschlichen Karzinome exprimierten das Antigen in dieser anomerischen Form. Die Kombination von synthetischen Antigenen und spezifisch gegen sie gerichteten monoklonalen Antikörpern liefert uns unschätzbare Werkzeuge für das Studium der Tumormarker-Expression in menschlichen und ihm entsprechenden tierischen Tumormodellen.